The colors of investors’ money: The role of institutional investors around the world - Ferreira, Miguel A.; Matos, Pedro (Journal of Financial Economics, 2008)
We study the role of institutional investors around the world using a comprehensive data set of equity holdings from 27 countries. We find that all institutional investors have a strong preference for the stock of large firms and firms with good governance, while foreign institutions tend to overweight firms that are cross-listed in the U.S. and members of the Morgan Stanley Capital International World Index. Firms with higher ownership by foreign and independent institutions have higher firm valuations, better operating performance, and lower capital expenditures. Our results indicate that foreign and independent institutions, with potentially fewer business ties to firms, are involved in monitoring corporations worldwide.